Grammatical errors across proficiency levels in the spoken English of matriculation students / Nurjasmin binti Mahidin Abd Kadir - Mahidin Abd Kadir, Nurjasmin (2014)
This study examines the grammatical errors made across proficiency levels in the spoken English of matriculation students in their oral test. This study attempts to identify and analyze the errors made by students from different levels of proficiency, ranging from lower intermediate, intermediate, upper intermediate and finally advanced. The specific objectives of this study are to identify the errors made by the students and to determine the frequency of occurrence of the different types of errors for each level of proficiency. The data were obtained from 32 group discussions in an oral test in the 13-week of the semester. The errors were analyzed using Dulay, Burt and Krashen’s (1982) surface strategy taxonomy, which specifies four ways by which students modify the target forms, namely through misformation, misordering, addition and omission. The key findings indicated that across proficiency levels, misformation and omission accounted for the majority of the total grammatical errors identified followed by addition and misordering being less frequent. In addition, verb form and word form related errors were found to be the two most frequent types of errors made by students across proficiency levels. The findings have important implications for L2 pedagogy as they can contribute to raise the awareness of teachers and curriculum developers of the types of grammatical errors made by students from different levels of proficiency in order that appropriate measures may be taken to address the problem.